Living Outside the Circle: The Politics of HIV/AIDS Education and the Disenfranchisement of HIV-Negative Gay Men - Kimberly B. Sessions (Adult Education Research Conference, 1999)
The purpose of this qualitative study was to use the lens of political planning theory to explore the relationship between how HIV-negative gay men think HIV/AIDS prevention efforts "should" be handled and how they actually are handled.